Predictive clinical factors of chronic peripheral neuropathy induced by oxaliplatin - Yildirim, Nilgun; Cengiz, Mahir (Springer, 2020)
Purpose We aimed to identify potential clinical parameters that can be easily obtained by a pre-treatment clinicopathological evaluation and whole blood test to estimate the development of oxaliplatin-induced peripheral neuropathy (OIPN). Methods This study was conducted retrospectively. For the FOLFOX regimen, patients received oxaliplatin, 85 mg/m(2), every 2 weeks for 12 courses, and with the XELOX regimen, oxaliplatin was 130 mg/m(2), every 3 weeks for 6-8 courses. The incidence and degree of neuropathy (NCI-CTCAE v.3) were recorded. Results A total of 186 patients were included in the study. There were 108 (58%) patients in the grade 0-1 (G0-G1) neuropathy group (mean age 50.5 +/- 11.5; 63% men), and 78 (42%) patients in the grade 2-3 (G2-G3) neuropathy group (mean age 58.0 +/- 10.8; 46.2% men). The relationship between G2-G3 OIPN development and age (p < 0.001), gender (p = 0.02), and ECOG performance status (p = 0.007) was statistically significant. In the G2-G3 neuropathy group, serum gamma-glutamyl transferase (GGT) (p < 0.001) and glucose (p = 0.007) levels were higher, whereas vitamin D (p < 0.001), hemoglobin (Hgb) (p < 0.001), serum albumin (p = 0.001), and serum magnesium (p = 0.035) levels were lower compared with the G0-G1 neuropathy group. G2-G3 neuropathy was observed in 88% of patients with mucinous carcinoma pathologic type (p < 0.001). Conclusion This study demonstrated that age, histopathologic type, albumin, GGT, glucose, vitamin D, and Hgb levels were the effective factors in prediction of the development of OIPN. In addition, GGT, vitamin D, and Hgb levels were the most effective factor to predict development of OIPN.
Keywords: Oxaliplatin; Peripheral neuropathy; Gastrointestinal system cancers; Treatment; Toxicity